Need For Constitutional Review To Accommodate Zakat And Waqf Laws In Nigeria - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad; Mashema, Bashir Liman; Muhammad, Anas Adam (UIN Kiai Haji Ahmad Sidiq Jember, 2024)
This paper investigates the fundamental elements of Islamic social welfare and economic systems Waqf and Zakat. As required almsgiving and charitable endowments, they are essential to wealth redistribution and communal support. Regardless of their relevance, the absence of official recognition and incorporation within the national legal system poses significant obstacles for these institutions in Nigeria. In an effort to increase the effectiveness and influence of Zakat and Waqf legislation in Nigeria, this study makes the case for a constitutional review that would include them. A qualitative research approach was taken, utilizing contents analysis for data analysis as well as literature and interview to obtain pertinent information. According to the research, the Nigerian constitution does not explicitly and immediately formalize the Waqf and Zakat institutions, and new legislation is required to enable their creation and management. The study offers a thorough analysis of pertinent federal laws and acts as a viable remedy to improve the Waqf and Zakat systems throughout Nigeria.